188W/188Re Generator System and Its Therapeutic Applications. (8th May 2014) - Boschi, A.; Uccelli, L.; Pasquali, M.; Duatti, A.; Taibi, A.; Pupillo, G.; Esposito, J.
Abstract : The 188 Re radioisotope represents a useful radioisotope for the preparation of radiopharmaceuticals for therapeutic applications, particularly because of its favorable nuclear properties. The nuclide decay pattern is through the emission of a principle beta particle having 2.12 MeV maximum energy, which is enough to penetrate and destroy abnormal tissues, and principle gamma rays (E γ = 155 keV), which can efficiently be used for imaging and calculations of radiation dose. 188 Re may be conveniently produced by 188 W/ 188 Re generator systems. The challenges related to the double neutron capture reaction route to provide only modest yield of the parent 188 W radionuclide indeed have been one of the major issues about the use of 188 Re in nuclear medicine. Since the specific activity of 188 W used in the generator is relatively low (<185 GBq/g), the eluted Re 188 O 4 - can have a low radioactive concentration, often ineffective for radiopharmaceutical preparation. However, several efficient postelution concentration techniques have been developed, which yield clinically useful Re 188 O 4 - solutions. This review summarizes the technologies developed for the preparation of 188 W/ 188 Re generators, postelution concentration of the 188 Re perrhenate eluate, and a brief discussion of new chemical strategies available for the very high yield preparation of 188 Re radiopharmaceuticals.